Beyond the Limit of Ideal Nernst Sensitivity: Ultra-High Sensitivity of Heavy Metal Ion Detection with Ion-Selective High Electron Mobility Transistors. (1st January 2018) - Chen, Yi-Ting; Hseih, Ching-Yen; Sarangadharan, Indu; Sukesan, Revathi; Lee, Geng-Yen; Chyi, Jen-Inn; Wang, Yu-Lin
Abstract : Exposure to heavy metal ions poses grave danger to public health and reliable and affordable water quality monitoring system that can rapidly screen for heavy metal ion contamination is necessary. In this research, we have developed a unique sensing methodology to detect heavy metal ions such as Pb 2+ and Hg 2+ in water sources, using ion-selective high electron mobility transistor sensor (ISHEMT). A detailed investigation of the sensing and selectivity characteristics of ISHEMT is carried out and a theoretical model is proposed for the illustration of the enhanced sensitivity and selectivity. The high field modulated ISHEMT sensor displays very high sensitivity, much beyond the ideal Nernstian slope, offering very low detection limit (10 −10 M for Pb 2+ and 10 −11 M for Hg 2+ ). The sensing characteristics are not affected by the presence of interfering ions and the selective sensor response has been validated using fixed interference and separate solution methods. These sensor characteristics are superior than the traditional ISE or ISFET sensors, and at par with laboratory standard technologies like ICP-MS. The miniaturized, inexpensive and user-friendly sensor technology can provide consumers with an affordable and convenient means of securing safe and contamination free water and food consumption.